Electroacupuncture Reduces Oocyte Number and Maintains Vascular Barrier Against Ovarian Hyperstimulation Syndrome by Regulating CD200 - Chen, Li; Huang, Xuan; Wang, Li; Wang, Cencen; Tang, Xu; Gu, Minghui; Jing, Jun; Ma, Rujun; Ge, Xie; Yao, Bing (Frontiers in Cell and Developmental Biology, 2021)
Ovarian hyperstimulation syndrome (OHSS) is a common complication caused by ovulatory stimulation therapy, which manifests as an increase in ovarian volume, an increase in the number of oocytes retrieved, and increased vascular permeability throughout the body and especially in ovarian tissue. In our previous study, we found that electroacupuncture (EA) could prevent the progression of OHSS, by mainly affecting ovary. However, the specific molecules and the mechanism of this process were still unknown. In order to explore the underlying mechanism, OHSS rat model was established and EA treatment was performed, which was followed by proteomic analysis of ovaries. Results showed a significant increase in the expression level of CD200 in the ovaries of OHSS group treated with EA than those of OHSS group. Clinical data showed that the level of CD200 in follicular fluid was negatively correlated with the number of oocytes retrieved and serum E2 level. Further in vitro experiments showed a concentration-dependent role of human chorionic gonadotropin (hCG) in reducing CD200 and CD200R levels, and increasing inflammatory cytokine levels in cultured KGN cells. In human umbilical vein endothelial cells (HUVECs), the vascular barrier function was improved by CM (cultural medium from KGN cell) which treated with CD200Fc (CD200R agonist). Meanwhile, the results of in vivo experiments indicated that EA reduced the number of ovarian corpora lutea, decreased inflammatory response, and improved the vascular barrier function by increasing the expression of CD200 and CD200R in rat ovaries. These findings suggest that EA treatment may reduce oocyte number and maintain vascular barrier against OHSS through ovarian anti-inflammatory response mediated by CD200. Therefore, this study is the first to identify CD200 as a main of EA in the ovary and elucidate the possible mechanism of EA on preventing and treating OHSS, which provide a scientific basis for CD200 as an effector and indicator in EA treatment.